2018
DOI: 10.1038/s41598-018-33319-9
|View full text |Cite
|
Sign up to set email alerts
|

Host lipid sensing promotes invasion of cells with pathogenic Salmonella

Abstract: Pathogenic Salmonella species initiate infection by invading non-phagocytic intestinal epithelial cells (IEC). This invasion is brought about by a number of Salmonella invasion promoting molecules (Sips) encoded by the Salmonella Pathogenicity Island - 1 (SPI-1). Intracellular delivery of some of these molecules also brings about caspase-1 – mediated pyroptotic cell death that contributes to pathogen clearance. These molecules are secreted and delivered inside cells upon contact of Salmonella with one or more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In contrast, cell free lysate (CFL) treatment to lettuce leaves from S. Typhimurium showed a classical MAMP based stomatal closure compared to live cell treatments, suggesting that cell free or secreted components from S. Typhimurium are recognized by plants to trigger innate response. The host sensing of cell free lysate from S. Typhimurium SL1344 was monitored and shown with human cells, wherein cell free lysates from S. Typhimurium SL1344 were recognized by the hosts leading to caspase-1-mediated proteolytic cell death contributing to pathogen clearance (Shivcharan et al, 2018). Interestingly, the heat-killed CFL treatment showed similar stomatal aperture as seen previously with live S. Typhimurium cells, suggesting that host sensing for innate stomatal defense requires secreted exo-metabolites.…”
Section: S Typhimurium Live Cells and Cell Free Lysate Treatment Indmentioning
confidence: 58%
“…In contrast, cell free lysate (CFL) treatment to lettuce leaves from S. Typhimurium showed a classical MAMP based stomatal closure compared to live cell treatments, suggesting that cell free or secreted components from S. Typhimurium are recognized by plants to trigger innate response. The host sensing of cell free lysate from S. Typhimurium SL1344 was monitored and shown with human cells, wherein cell free lysates from S. Typhimurium SL1344 were recognized by the hosts leading to caspase-1-mediated proteolytic cell death contributing to pathogen clearance (Shivcharan et al, 2018). Interestingly, the heat-killed CFL treatment showed similar stomatal aperture as seen previously with live S. Typhimurium cells, suggesting that host sensing for innate stomatal defense requires secreted exo-metabolites.…”
Section: S Typhimurium Live Cells and Cell Free Lysate Treatment Indmentioning
confidence: 58%
“…The relatively high glucose concentration in the proximal small intestine can inhibit SPI-1 gene expression via Mlc, perhaps together with PhoBR and/or SirA (Agbor and McCormick, 2011). Lysophosphatidylcholine released following caspase-1 activation in Salmonella -infected cells promotes the expression of Sips and HilA and increases Salmonella invasion of host cells, and it is regarded as a key component of a novel regulatory mechanism for the regulation of cellular invasion with pathogenic Salmonella (Shivcharan et al, 2018).…”
Section: The Regulation Of Spi-1mentioning
confidence: 99%
“…Recently, Shivcharan et al (2018) demonstrated that LPC promotes the invasive ability of Salmonella by enhancing the Salmonella invasion-promoting molecules spiA and spiC. In addition, LPC continuously maintains the expression of hilA, one of the major transcription factors of Sips.…”
Section: Discussionmentioning
confidence: 99%